Prediction of Gas Hydrate Formation at Blake Ridge Using Machine Learning and Probabilistic Reservoir Simulation. (8th April 2021) - Eymold, William K.; Frederick, Jennifer M.; Nole, Michael; Phrampus, Benjamin J.; Wood, Warren T.
Abstract: Methane hydrates are solid structures containing methane inside of a water lattice that form under low temperature and relatively high pressure. Appropriate hydrate‐forming conditions exist along continental shelves or are associated with permafrost. Hydrates have garnered scientific interest via their potential as a source of natural gas and their role in the global carbon cycle. While methane hydrates have been collected in multiple diverse geographic settings, their quantities and distribution in sediments remain poorly constrained due to sparse relevant data. Using statistical and machine learning approaches, we have developed a workflow to probabilistically predict methane hydrate occurrence from local microbial methane sourcing. This approach utilizes machine‐learned global maps produced by the Global Predictive Seabed Model (GPSM) as inputs for the statistical sampling software, Dakota, and multiphase reservoir simulation software, PFLOTRAN. Dakota performs Latin hypercube sampling of the GPSM‐predicted values and uncertainties to generate unique sets of input parameters for 1‐D PFLOTRAN simulations of gas hydrate and free gas formation resulting from methanogenesis to steady state. We ran 100 1‐D simulations spanning a kilometer in depth at 5, 297 locations near Blake Ridge. Masses of hydrate and free gas formed at each location were determined by integrating the predicted saturation profiles. Elevated hydrate formation is predicted to occur at depths >500 meters below sea level at this location, and is strongly associated with high seafloor total organic carbon values. We produce representative maps of expected hydrate occurrence for the study area based on multiple realizations that can be validated against geophysical observations. Plain Language Summary: Gas hydrates represent an important component of the global carbon budget, but uncertainties exist regarding their geographic occurrence and estimated volume. To incorporate these uncertainties into numerical simulations, we statistically sampled multiple seafloor geophysical values and determined the likelihood of gas hydrate and free gas formation in seafloor sediments. We compared our results to previous simulations as verification of our calculations; specifically, we find strong correlations between gas hydrate formation and the sedimentation rate and total organic carbon at the seafloor. We used the frequency of simulations where hydrate forms as well as the estimated volume of formation to produce probability maps of gas hydrate occurrence in an analogous way to weather forecast maps. These maps in turn can identify new areas of hydrate interest without the economic and environmental costs associated with oceanic drilling in sensitive geographic areas. Predictions of both gas hydrate and free gas occurrence can improve global estimates related to the carbon budget, improve our understanding of the effects of hydrate and gas on sediment seismic velocity, and identify seafloor hazards even when limited data are available. Key Points: Coupling of Dakota and PFLOTRAN incorporates uncertainties into numerical simulations of gas hydrate formation near Blake Ridge Maps of gas hydrate or free gas occurrence in seafloor sediments correlate to sedimentation rate, total organic carbon, and heat flux Open source framework can be extended to new geographic regions to improve predictions of global volumetric estimates of gas hydrate